Computer Science and Programming Courses in Geography Departments in the United States. - Bowlick, Forrest J.; Goldberg, Daniel W.; Bednarz, Sarah Witham (Professional Geographer, 2017)
Geographic information systems (GIS) are fundamental information technologies. The capabilities and applications of GIS continue to rapidly expand, requiring practitioners to have new skills and competencies, especially in computer science. There is little research, however, about how best to prepare the next generation of GIScientists with adequate computer science skills. This article explores how U.S. geography departments are introducing and developing computer science and programming skills in their geography and GIS degree programs. We review the degree requirements in fifty-five geography departments and discover that forty-four of them offer some kind of GIS programming course. Of the 210 separate degree options identified, however, only 22 require one of these courses for a degree. There is little consistency or emphasis on computer science and programming skills in geography or GIS degrees, despite the immense importance of these components in geography and GIS careers. We propose future research along distinct investigative tracks to build a research-based understanding of the educational interactions among GIS, computer science, programming, and geography.